Installing and managing workable knowledge management systems - Rubenstein, Albert H., 1923-2013 (Praeger, 2003)
Every organization should have some method of capturing, storing, transforming, retrieving, and using knowledge and lessons learned. This book has been written to help managers throughout the organization to design and develop knowledge management systems that are effective and lasting. Successful knowledge management systems are integrated into the corporate culture and the existing information systems apparatus. They are introduced gradually, so as not to clutter the testing phase with too many details. And simple and appropriate metrics are utilized at each stage of the design and operating.